(4 + 2x)(6 + 2x) =
4(6 + 2x) + 2x(6 + 2x) =
24 + 8x + 12x + 4x^2 =
4x^2 + 20x + 24 <==
Answer: Store C by far, less money more time.
Step-by-step explanation:
How To Find Inverses:
1. First, replace f(x) with y . ...
2. Replace every x with a y and replace every y with an x .
3. Solve the equation from Step 2 for y . ...
4. Replace y with f−1(x) f − 1 ( x ) . ...
5. Verify your work by checking that (f∘f−1)(x)=x ( f ∘ f − 1 ) ( x ) = x and (f−1∘f)(x)=x ( f − 1 ∘ f ) ( x ) = x are both true.
Answer:
-319
Step-by-step explanation:
5/8=0.625
7/12=0.583......
5/8 is bigger as ive put both into a decimal as it is easier to tell